Neuropathic pain - V. A. Koriachkin; A. P. Spasova; V. V. Khinovker (Инновационная медицина Кубани, 2021)
Background Chronic neuropathic pain is a common occurrence, its prevalence ranges from 7 to 10% of the total population. Currently, the only official document that includes neuropathic pain is the International Classification of Headaches Disorders (ICHD-3), in which this type of pain is associated with traumatic brain injury and neuralgia. Until now, there has been no generally accepted terminology and classification of chronic neuropathic pain.Objective To provide the current terminology, classification and additional characteristics of neuropathic chronic pain.Results The review of modern terminology and classification of neuropathic chronic pain describes the terms included in the concept of chronic peripheral and central neuropathic pain, identifies pain subtypes, as well as its additional characteristics such as the intensity of neuropathic pain, the severity of suffering and disability.Conclusions Thus, the presented recent classification of chronic neuropathic pain is an exhaustive list of the most common neuropathic pain syndromes. The inclusion of classification into clinical practice will help to draw attention to the problem of treatment of chronic neuropathic pain by WHO members, carrying out epidemiological studies and making a correct diagnosis, and therefore the appointment of adequate treatment methods.